PENGARUH AUDIT TENURE DAN REPUTASI KAP TERHADAP AUDIT REPORT LAG DENGAN SPESIALISASI INDUSTRI AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Industri Jasa yang Terdaftar di Bursa Efek Indonesia Tahun 2016 – 2018) - Pearlytha Mayling; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2020)
Reputation on audit report lag and the impact of auditor industry specialization on the association between audit tenure and audit report lag. The dependent variable used in this study is the audit report lag. Audit tenure and Accounting Public Firm’s Reputation used as independent variables. This study also used the auditor industry specialization as a moderating variable. The sample in this study consists of 357 companies which included in the Service Industry that listed on the Indonesia Stock Exchange in the period 2016-2018. The data used in this study was secondary data and selected by using proportionate stratified random sampling. The technique of analysis that used to examine the hypothesis was multiple regression analysis Based on this study, the results show that audit tenure has a negative significant influence on audit report lag and Accounting Public Firm’s reputation has no significant influence on audit report lag. This study results also show that the auditor industry specialization has a moderating effect on the association between audit tenure and audit report lag.